2013
DOI: 10.5750/jgbe.v6i2.582
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Demand for Gambling/Office Football Pool Betting in Ibadan, Oyo State, Nigeria

Abstract: In the present study, we evaluated the statistical significance of a number of socioeconomic and demographic variables on the demand for office football pool betting in Ibadan, Oyo State of Nigeria. The Ordinary Least Square (OLS) econometric model was employed. The study identifies the socioeconomic and demographic characteristics of the gamblers and econometrically analyzed the factors influencing gambling activities. The results showed that gender, age, household size, educational attainment, occupation, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…Croups et al (1998), Ghent and Grant (2006), and Giacopassi et al (2006) found the presence of a negative relationship between educational attainment and lottery consumption. The result was consistent with the findings by Albers and Hubl (1997), Clotfelter and Cook (1990), and Nwigwe et al (2012) who discovered that gambling activity fell with formal education. Raymond (1994) found purchasers of lottery tickets to be moderately well-educated.…”
Section: Review Of Literaturesupporting
confidence: 92%
See 3 more Smart Citations
“…Croups et al (1998), Ghent and Grant (2006), and Giacopassi et al (2006) found the presence of a negative relationship between educational attainment and lottery consumption. The result was consistent with the findings by Albers and Hubl (1997), Clotfelter and Cook (1990), and Nwigwe et al (2012) who discovered that gambling activity fell with formal education. Raymond (1994) found purchasers of lottery tickets to be moderately well-educated.…”
Section: Review Of Literaturesupporting
confidence: 92%
“…This finding was consistent with those by Clotfelter and Cook (1989), Delfabbro (2000), Kaizeler and Faustino (2010), and Kearney (2002). With respect to occupation, the study by Nwigwe et al (2012) shows that people with more lucrative occupations gambled less. Albers and Hubl (1997), Clotfelter and Cook (1990), and Worthington (2001) also found the same result and discovered that skilled and unskilled workers gambled more than intellectuals.…”
Section: Review Of Literaturesupporting
confidence: 90%
See 2 more Smart Citations